Detection of Bone Defects Using CBCT Exam in an Italian Population. (17th October 2017) - Gambarini, Gianluca; Miccoli, Gabriele; Gaimari, Gianfranco; Pompei, Deborah; Pilloni, Andrea; Piasecki, Lucila; Al-Sudani, Dina; Di Nardo, Dario; Testarelli, Luca
Abstract : Background . The aim of this study was to evaluate the in vivo incidence and the location of fenestrations in a young Italian population by using CBCT. Materials and Methods . Fifty patients who had previously performed CBCT for planning third molar extraction or orthodontic therapy were selected for the study. No previous dental treatment had been performed on these patients. Overall, 1, 395 teeth were evaluated. Root fenestrations were identified according to the definition of Davies and the American Association of Endodontists. Data was collected and statistically analyzed. Results . Fenestrations were observed in 159 teeth out of 1, 395 (11% of teeth). In the lower jaw, we found 68 fenestrations (5%) and 91 in the maxilla (6, 5%). Incisors were the teeth with the highest incidence of fenestrations. Conclusion . The relative common finding (11%) of fenestration supports the need for CBCT exams before any surgical/implant treatment to avoid complications related to the initial presence of fenestrations. CBCT was found to be an effective and convenient tool for diagnosing fenestration.